Manajemen Sistem Penilaian dan Pelaporan Pembelajaran Daring di SMA (Studi Kasus di SMA Negeri 1 Cilacap) - Hidayat, Ayi Najmul; Ratnawulan, Teti; Aljihad, Fuad; Heri, Heri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This research is motivated by the demands of digitalization in the technological era which require speed of service, honesty, and the demands of the times. This is supported by the Director General of Elementary and Primary Education through the Circular of the Director General of Elementary and Basic Education of the Ministry of Education and Culture Number: 08/D/KR/2017 concerning filling in the final grades of report cards, US and USBN in Dapodik, especially at the high school level, so all high schools that have been appointed to use e-reports starting in 2017 must insert and upload data on report cards, US, and USBN, including SMA Negeri 1 Cilacap. This study aims to obtain an overview and analysis of the planning, organization, and implementation of learning assessment management in a bold manner at SMA Kabupaten Cilacap (Case Study at SMAN 1 Cilacap). SMAN 1 Cilacap is one of the schools that has implemented e-reports at the high school level of around 1,400 (Total SMA in Indonesia 13,000 schools) and the reporting. The method used in this study uses a descriptive qualitative approach. This research was conducted by implementing the management principles of G.R. Terry, namely planning, organizing, implementing, and supervising the assessment and reporting of student learning outcomes by using IT. The research method used is a qualitative approach. In conclusion, at all stages of management, planning, organizing, and carrying out assessment and reporting of learning outcomes has been carried out together with the school element approach, coordinated by the school through a curriculum team that collaborates with school management, school development teams, assisted by deputy principals, and curriculum teams , as well as with all the teachers. The obstacles faced, namely HR and technical constraints and can be overcome with assistance by the IT team together with the teachers. In its implementation, technical problems usually occur at the beginning of use. Keywords: management, assessment, courage.